Momentum and Reversals in Equity‐Index Returns During Periods of Abnormal Turnover and Return Dispersion - Connolly, Robert; Stivers, Chris (Journal of Finance, 2003)
ABSTRACT We document new patterns in the dynamics between stock returns and trading volume. Specifically, we find substantial momentum (reversals) in consecutive weekly returns when the latter week has unexpectedly high (low) turnover. This pattern is evident in equity indices, index futures, and individual stocks. Similarly, we also find that the autocorrelation in equity‐index returns is increasing with the unexpected dispersion across the latter week's firm‐level returns. Weeks with extreme turnover and dispersion shocks (both high and low) tend to have more macroeconomic news releases. Our findings bear on understanding price formation and the economic interpretation of turnover and dispersion shocks.